Thinking abilities and their relation to the self-regulated learning in education students from a public university of Lima - Vicuña Rau, Milagros Virginia (2019)
The main purpose that guides the development of the current investigation was to establish if the thinking abilities are related to the self-regulated learning, in a sample of 284 students from the Education Faculty of a Public University of Lima. For that reason, a non-experimental design was used, of a correlational type. To the chosen sample were applied the Questionnaire of Thinking Abilities of Alberto Acevedo and Marcela Carrera, and the Questionnaire of Self-Regulation for learning of Juan Carlos Torre. These instruments had their levels of validity and reliability previously determinated through a pilot test, which showed that both of them fulfill both conditions. The statistical analyses, made using the software SPSS version 24, show that the proposed hypotheses have been validated; this means that the thinking abilities are related to the self-regulated learning in the studied sample, both at the general level (r = 0,75) and at each one of the dimensions that compose each one of these variables.